A long pitch home - Lorenzi, Natalie Dias (Charlesbridge, 2018)
Ten-year-old Bilal preferred life in Pakistan where he was the star of his cricket team and his family was all together. Now he's living in America with his aunt and uncle while his father remains in Pakistan. Hoping to fit in and keep up with her American cousin Jalaal, Bilal joins the baseball team where he is determined to stand out as a pitcher--perhaps then his father would come to America to watch him play.